cDNA cloning and functional activity of a glucocorticoid-regulated inflammatory cyclooxygenase. - O'Banion, M K (1992)
The antiinflammatory glucocorticoids are potent inhibitors of cyclooxygenase, a key regulator of prostaglandin synthesis; yet, the mechanism(s) by which this occurs is not fully understood. We have cloned a 4.1-kilobase (kb) cDNA, distinct from the previously cloned cyclooxygenase (2.8 kb), that confers cyclooxygenase activity to transfected cells. The mRNA for this newly discovered cyclooxygenase is unique for its long 3' untranslated region containing many AUUUA repeats. Levels of the 4.1-kb cyclooxygenase mRNA are rapidly increased by serum or interleukin 1 beta in mouse fibroblasts and human monocytes, respectively, and decreased by glucocorticoids, whereas levels of the 2.8-kb cyclooxygenase mRNA do not change. Similar effects are seen in the presence of cycloheximide where the 4.1-kb, but not the 2.8-kb, mRNA is greatly superinduced. Thus, there are both constitutive (2.8 kb) and regulated (4.1 kb) cyclooxygenase species, the latter most likely being a major mediator of inflammation.